Nas teias do imaginário amazônico: uma perspectiva poética da obra água da fonte de João de Jesus Paes Loureiro - SILVA, Keise Barreto da (2021)
The present study aims to analyze the work Água da Fonte, work of the paraense writer João de Jesus Paes Loureiro, basing the analysis, mainly, in the researches of the author about the Amazonian imagination in order to explore the representativeness of the city of Abaetetuba at work and in the imagination. The theoretical framework used to conduct this research is based on studies of Loureiro (2008), Eliade (2002), Tupiassú (2005), Souza (2014), among other important authors submitted in the course of work. The research of a qualitative nature, was initiated by the justification of the necessity of the course of Letters - Portuguese Language of the Federal University of Pará Campus in Abaetetuba, provide greater relevance of the studies on the Literature of the Amazonian expression in its curriculum, once the institution is located in the region of Baixo Tocantins, in the Amazon. The result of this restlessness turned in this monograph, which was built in three chapters in order to explain about the poetic of the author Paes Loureiro and their contributions to the culture and the imaginary, the presence of literature in the Amazon so regional and universal in the propagation of poetry and, finally, the analysis of some poems of the work that had been chosen for the composition of the work.